Ứng dụng mô hình dạy học kết hợp trong dạy học chủ đề “Hệ vận động”, phần Vật sống, Khoa học tự nhiên 8 - Phạm, Thị Mỹ Duyên; Lê, Thị Phượng (Tạp chí Giáo dục, 2024)
The article focuses on the application of the blended learning model in teaching the topic “The Musculoskeletal System” in Grade 8 Natural Science. Blended learning is a combination of traditional and online teaching, leveraging modern technology to enhance teaching effectiveness. The article emphasizes the importance of utilizing digital learning resources such as videos, 3D images, and simulations to convey complex content related to the human body, making it easier for students to grasp the material. The study analyzes and synthesizes theories on the blended learning model, while also proposing a lesson design process that ensures a balance between theory and practice. The results indicate that this model not only improves students’ self-learning competence and creative thinking but also serves as an effective approach in modern education, especially for subjects requiring a high degree of visualization like Natural Science.